THE LISTENING COMPREHENSION PROBLEM OF VOCATIONAL STUDENTS - Rumaidin Sikumbang; Asnawi; Say Pulma Tamba; Yurika Rahayu Ritonga; Irwansyah Zega (LPPI UMN AL WASHLIYAH, 2025)
Studying English in Vocational high school has certain characteristics related to the novices' major. English as a foreign language has an essential role to be mastered by the students. The orientation of the students after graduating from school commonly gets a job related to their competency. This research investigated the main problem of listening comprehension in English as a foreign language faced through vocational high school students. The qualitative methodologies have been implemented in this examine with questionnaires and interviews used an instruments for collecting information. The findings display that the foremost troubles of information the spoken text are the vocabulary and prononciation. The findings of this observe is expected to provide valuable information for English teachers regarding to the listening difficulties faced by vocational students, which enable them to help students to improve their listening capabilities.